Pengembangan Media Pembelajaran Berbasis Multimedia Pada Mata Kuliah Pemesinan NC di Program Studi Pendidikan Teknik Mesin Universitas Negeri Jakarta - Aditya Wahyu Wardhana; Syaripuddin; Lukman Arhami (Risenologi, 2021)
Learning media has a very important role in teaching and learning activities. Learning media is a medium to convey knowledge to students. In the current era of the COVID-19 pandemic, learning media must be able to make students obtain optimal learning outcomes. The purpose of this study was to produce learning media in NC machining courses and to determine the feasibility of learning media in NC machining courses. This study uses the Research and Development method with the main subject being students of the Mechanical Engineering Education Study Program, Faculty of Engineering, Jakarta State University who take NC machining courses. The instrument used in this study was a questionnaire in the form of a google form. The results showed that the percentage score obtained from material experts was 78.6% and the percentage score obtained from media experts was 72%. These results also show that the media and materials used in the application of NC learning media are said to be valid. In addition, in the small group trial the score obtained was 91.73%. The score also indicates that the application has been felt practical. Likewise in the field trial, where the score obtained is 84.20% or it can be interpreted that the application has been felt practical by the majority of users. So, based on these results, it can be concluded that the application of multimedia-based NC learning media is feasible to use.